2006
DOI: 10.1002/cbf.1220
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and enzymic–non-enzymic antioxidant responses in children with acute pneumonia

Abstract: In this article, oxidative stress and enzymic-non-enzymic antioxidants status were investigated in children with acute pneumonia. Our study included 28 children with acute pneumonia and 29 control subjects. The age ranged from 2 to 11 years (4.57+/-2.13 years) and 2 to 12 years (4.89+/-2.22 years) in the study and control groups, respectively. Whole blood malondialdehyde (MDA) and reduced glutathione (GSH), serum beta-carotene, retinol, vitamin C, vitamin E, catalase (CAT), ceruloplasmin (CLP), total bilirubin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 25 publications
(26 reference statements)
1
38
1
1
Order By: Relevance
“…The presence of clinical pathologies 37 , the clinical condition of the patient before arriving at the operating room, the surgical trauma itself 38,39 , and fasting, mentioned earlier, are important factors in the promotion of this imbalance. A particular clinical situation involving the use of sevoflurane should not be forgotten: the use of this halogenated compound in individuals with erythrocyte deficiency of G6PD 40 .…”
Section: Discussionmentioning
confidence: 98%
“…The presence of clinical pathologies 37 , the clinical condition of the patient before arriving at the operating room, the surgical trauma itself 38,39 , and fasting, mentioned earlier, are important factors in the promotion of this imbalance. A particular clinical situation involving the use of sevoflurane should not be forgotten: the use of this halogenated compound in individuals with erythrocyte deficiency of G6PD 40 .…”
Section: Discussionmentioning
confidence: 98%
“…Others studies have also demonstrated an increase of lipid peroxidation products in whole blood of these patients. Accordingly, increased serum MDA levels in acute pulmonary infection have been reported in both children (Cemek et al, 2006), and in adult patients . The molecular mechanism of damage in CAP included various mediators.…”
Section: Discussionmentioning
confidence: 99%
“…In CAP, the role of glutathione in the pathogenesis of microorganism invasion or antioxidant non-enzymatic response has not been characterized. Cemek et al (2006), studied antioxidant status in children with acute pneumonia, fi nding that all antioxidant compounds were decreased, i.e. vitamin C, vitamin E and GSH levels, compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…24 Serum TAS was also reported to be decreased in pneumonia patients, with the decline associated with increased severity of the disease. 25 Antioxidant molecules can prevent or inhibit the aforementioned harmful reactions. Although serum concentrations of different antioxidants can be measured separately, the measurement of TAS is more practical .…”
Section: Discussionmentioning
confidence: 99%